A Framework of Deploying Blockchain in Wireless Sensor Networks - Nguyen, Minh; Nguyen, Cuong; Tran, Hoang T. (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2022)
The most critical needs for wireless sensor networks (WSNs) are security, privacy, dependability, and autonomy. The networks might be vulnerable to hostile users and harmful usage if these problems are not ensured. Attacks and hazards are higher with centralized WSNs, particularly when data is shared with other businesses and sent between devices. In this paper, a WSN model with integrated blockchain security technology is proposed. Blockchains store the identity of each node. The validation is done by public blockchains and private blockchains. For sensor nodes, the authentication is implemented on the private blockchain. The public blockchain is used to authenticate cluster heads. Performing network attacks can easily be performed by unregistered nodes to access resources in the network. Broadcasting false information on the path of malicious nodes can increase packet latency and reduce packet delivery rate. In this paper, the model recommends the most secure nodes in the network to be used for secure routing. The main purpose is to reduce the attack of hackers from outside the network, improve the efficiency of detecting malicious nodes.